Diversity, distribution, and conservation status of Macrobrachium shrimp in freshwater ecosystems of Aceh, Indonesia - Dedi Fazriansyah Putra; Muhammadar Abdullah Abbas; Tongku Nizwan Siregar; Daisy Wowor (Veterinary World)
Background and Aim: Freshwater shrimps of the genus Macrobrachium play key ecological and socioeconomic roles in tropical freshwater ecosystems. However, their diversity, habitat associations, and conservation status remain understudied in Aceh Province, Indonesia. This study aimed to (1) assess the diversity and morphometric variation of Macrobrachium species, (2) map their distribution across lotic and lentic habitats in Aceh, (3) Assess the impact of environment variable on species composition and richness and (4) evaluate their conservation status based on the International Union for Conservation of Nature (IUCN) criteria and local environmental threats.